No robust multispecies coexistence in a canonical model of plant–soil feedbacks. (30th May 2022) - Miller, Zachary R.; Lechón‐Alonso, Pablo; Allesina, Stefano
Abstract: Plant–soil feedbacks (PSFs) are considered a key mechanism generating frequency‐dependent dynamics in plant communities. Negative feedbacks, in particular, are often invoked to explain coexistence and the maintenance of diversity in species‐rich communities. However, the primary modelling framework used to study PSFs considers only two plant species, and we lack clear theoretical expectations for how these complex interactions play out in communities with natural levels of diversity. Here, we extend this canonical model of PSFs to include an arbitrary number of plant species and analyse the dynamics. Surprisingly, we find that coexistence of more than two species is virtually impossible, suggesting that alternative theoretical frameworks are needed to describe feedbacks observed in diverse natural communities. Drawing on our analysis, we discuss future directions for PSF models and implications for experimental study of PSF‐mediated coexistence in the field. Abstract : Plant–soil feedbacks (PSFs) are considered a key mechanism generating frequency‐dependent dynamics in plant communities, but the primary modelling framework used to study PSFs considers only two plant species, and we lack clear theoretical expectations for communities with natural levels of diversity. Here, we demonstrate that this canonical model for PSFs is equivalent to a well‐studied model from evolutionary game theory, and use this equivalence to characterise the dynamics with an arbitrary number of plant species. Surprisingly, we find that the coexistence of more than two species is virtually impossible, suggesting that alternative theoretical frameworks are needed to describe feedbacks observed in diverse natural communities